Análise bioeconômica da produção de novilhos precoces de diferentes grupos genéticos terminados em confinamento, em Paragominas, Pará - MAIA, Janaina Teles da Silva (Universidade Federal do Pará, 2017)
The aim of this study was to evaluate the feasibility of a system of early termination of steers, in feedlot from, zootechnical and economic indicators, as well as compare the performance of different genetic groups (crosses with zebu and taurine). The study was conducted on private property in the municipality of Paragominas, Pará, which were used in the experiment the animals own production system, randomly selected from three genetic groups: Nellore, ½Angus ½Nellore e ½Charolais ½Nellore, but with date of birth and approximate weight, ie, the same contemporary group. The experiment was conducted in 2012 and 2013 with animals from birth, 2010 (67 animals) and 2011 (63 animals), respectively, all with an average age of 21 months at the beginning of feedlot season. To evaluate the production performance animals were weighed every 28 days, following a solids fasting period of 16h. Each week samples of concentrated feed, silage, and total diet (silage + concentrate) for analysis bromatological were collected. Economic data were collected on the property, and tabulated and analyzed in MS Excel. The results showed especially the animals crossing ½Charolais ½Nellore as the medium of performance indicators, statistically not differing in some aspects from the crossing ½Angus ½Nellore junction, but always with higher values. As for economic data showed positive indicators feedlot for two years of the experiment, with profitability and average return of 8.5% and 9%, respectively, highlighting the genetic group ½Charolais ½Nellore, as the most profitable, due to higher carcass yield.